Obesity and exercise immunology: implication in times of COVID-19 pandemic - Guilherme Gomes Azizi; Marco Orsini; Sérgio Duarte Dortas; Sandro de Albuquerque Cerbino (2020)
Obesity is a major worldwide epidemic, which places a burden on society and the public health system, affecting people of all ages and all social groups in developed and developing countries, reaching 650 million worldwide [1]. Thereby, we discuss the association between obesity inflammatory state and SARS-COV-2 infection, and the role of exercise immunology as a weapon and fundamental character to the health for million people in this pandemic time....